2007
DOI: 10.1590/s0066-782x2007000100004
|View full text |Cite
|
Sign up to set email alerts
|

Pacientes com angina instável tratados por meio de intervenções coronarianas percutâneas no novo milênio: o que os caracteriza?

Abstract: Objective: To identify clinical and angiographic profiles of patients with unstable angina seen at a tertiary hospital and treated with percutaneous coronary intervention (PCI). Methods:Study of a consecutive series of 1413 patients, selected from a computerized database, who underwent percutaneous revascularization in the three-year period of [2002][2003][2004]. There were no inclusion/exclusion criteria.Results: Systemic arterial hypertension (74%) and hypercholesterolemia (65%) were the classical risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In a Brazilian study carried out in São Paulo 20 , which evaluated 1,413 patients with unstable angina submitted to coronary angioplasty, the predominance of the male sex was also observed (62%), with a mean age of 61 years; however, the frequency of multivascular lesions was lower (42%). Other authors in a study carried out in patients with Ami in the city of Niteroi 21 found almost the same percentage of male sex patients (66.8%), also with a lower percentage of multivascular disease (54.9% in men and 63.3% in women).…”
Section: Discussionmentioning
confidence: 99%
“…In a Brazilian study carried out in São Paulo 20 , which evaluated 1,413 patients with unstable angina submitted to coronary angioplasty, the predominance of the male sex was also observed (62%), with a mean age of 61 years; however, the frequency of multivascular lesions was lower (42%). Other authors in a study carried out in patients with Ami in the city of Niteroi 21 found almost the same percentage of male sex patients (66.8%), also with a lower percentage of multivascular disease (54.9% in men and 63.3% in women).…”
Section: Discussionmentioning
confidence: 99%
“…Why these therapeutic alternatives do not always work?’ We believe that there are at least, five aspects pertaining to this inquiry: 1) The lack of consideration of existing ‘guidelines’ or ‘evidence based medicine’ regarding the accepted treatment options available; 2) lack of knowledge of different vasodilatation mechanisms; 3) the possibility of a crosstalk between different vasodilatation mechanisms; 4) the soluble guanylyl cyclase (sGC) enzymatic activity and; 5) the common use of MB as a ‘rescue’ or ‘ultimate’ therapeutic attempt. 6 …”
Section: The Cgmp/camp “Crosstalk” Is Underestimatedmentioning
confidence: 99%